Genetic analysis of LIPL32 as the target gene in the development of biodiagnostic assays for leptospirosis - Bahaman, Abdul Rani; Lee, S. V. (Veterinary Association Malaysia, 2011)
Definitive identification of pathogenic leptospires is crucial to instigate treatment and control of leptospirosis. Polymerase chain reaction (PCR) which is considered as a sensitive and specific assay has been useful in the rapid identification of pathogenic leptospires. The lipL32 gene encoding major outer membrane protein is an ortholog gene in all pathogenic leptospires. Construction of a precise evolutionary tree based on the complete /ipL32 gene sequence presents useful information in understanding the genetic evolution of pathogenic strains which facilitate the design of a definitive diagnostic assay. This present study showed the significance of /ipL32 gene and its application as the most suitable target in diagnostic assays for pathogenic leptospires. A comparative study was conducted via PCR using primers covering the /ipL32 gene. Amplicons of the correct size were cloned and sequenced foIlowed by bioinformatics analysis. Comparison of /ipL32 DNA sequence revealed a high degree of sequence conservation with an average DNA sequence identity of 97.8%. Three field isolates obtained were shown to have their origin from a common ancestor. This study is believed to be the first investigation involving the complete /ipL32 gene among pathogenic species in the genus Leptospira.